ANALYSIS OF CONTENT HEAVY METALS IN VARIOUS FISH SPECIES IN BATANG TORU RIVER, AEK PAHU TOMBAK AND AEK PAHU HUTAMOSU DISTRICT SOUTH TAPANULI - Sirait, Hariadi; Barus, Ternala A; Wahyuningsih, Hesti (Jurnal Perikanan dan Kelautan, 2013)
Research about content of heavy metals in various fish species have been done inBatang Toru River, Aek Pahu Tombak and Aek Pahu Hutamosu district South Tapanuliin March-April 2013. The purpose of this study was to determine the content of heavymetals that accumulate in the body of fish and the water, and to determine the waterquality of River Batang Toru, Aek Pahu Tombak and Aek Pahu Hutamosu. The methodfor determining the location of sampling for fish sample is "Purposive RandomSampling" in 6 (six) observation stations. Analysis of heavy metal analyzed on fishmeat and water using Atomic Absorption Spectrophotometric (AAS). The resultsshowed that the content of heavy metal in fish body didn’t exceeded the qualitystandard by SNI/7387/2009. Content of heavy metals accumulated in the water didn’texceeded the quality standard based on Regulation No.82 of 2001. Aek Pahu TombakRiver has a very good quality of water but Batang Toru River and Aek Pahu Hutamosuhave a good quality of water.